NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Food-derived curcumin selectively remodels LPS-induced metabolic reprogramming in MH7A synoviocytes: Multi-omics contextualization of rheumatoid arthritis-relevant inflammatory networks - Haobo Yuan; Yuting Tan; Yuanyuan Wang; Da Han; Xinli Zhou; Hao Han; Zhongshang Guo (Food Bioscience, 2026)

Alcohol and high-fat diet aggravate colitis-induced liver injury via glucocorticoid/IL-6-SAA1 axis in mice - Mingrui Zhao; Han Li; Xinghua Gao; Huijuan Da; Xun Cui; Dongquan Jing; Qixiang Zhao; Ying Wang; Yanling Guo; Zhenhua Gao; Shentian Zhuang; Qiuhua Cao (Food and Chemical Toxicology, 2026)

An orally administered colon-targeted mesalamine nano-prodrug for enhanced therapy and prevention of inflammatory bowel disease - Xiao-Han Tian; Da-Yuan Wang; Si-Yu Li; Shuna Cao; Feng Liu; Mingqing Zhang; Linqi Shi (Chemical Engineering Journal, 2026)

Removal efficiency and mechanisms of natural mineral materials for bacteriophages MS2 and ΦX174 in aqueous environments - Ying Song; Ya-ting Wang; Ying Han; Rong-xuan Xu; Yang Wang; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Evolution of PM2.5 chemical composition during summer new particle formation in a coastal city in the yangtze river delta: insights from pollution episodes, machine learning, and air mass origins - Han Zhou; Yichen Lu; Zeyi Li; Honglei Wang; Lijuan Shen; Yue Chen; Deyu Liu; Da Xu (Environmental Research, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Photothermal Agents in Cancer Therapy: Applications and Development Prospects - Shiyu He; Shuaipeng Feng; Yiming Han; Qingqing Xu; Jiaru Lan; Donghua Di; Da Wang; Siling Wang; Huan Zhai; Qinfu Zhao (Chemical Engineering Journal, 2026)

Application of Fourier transform near-infrared (FT-NIR) spectroscopy and machine learning for non-destructive viability assessment of 20-year stored Pinus densiflora seeds - Da-Eun Gu; Ja-Jung Ku; Sim-Hee Han (New Forests, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Artificial intelligence-enabled machine olfaction for volatile profiling and food quality decision-making - Yitian Gao; Jun-Hu Cheng; Han Wang; Yuandong Lin; Jinhua Wang; Da-Wen Sun (Food Chemistry, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Depth-dependent attachment and transport of bacteriophages MS2 and ΦX174 in saturated soils: Impacts of silt and clay fraction - Xue-yan Hao; Ying Han; Ying Song; Rong-xuan Xu; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Botryosphaeria dothidea: comprehensive understanding of its pathogenicity, resistance mechanisms, and management strategies in apple cultivation - Peng-Liang Han; Hou-Chao Wang; Hao Wu; Shuo-Chen Chai; Si-Qi Xu; Lei Yu; Da-Gang Hu (Planta, 2026)

Multi-target neuroprotective effects of Yukgunja-Tang (Liujunzi Decoction) in a mouse model of vascular dementia: Behavioral, glial, and transcriptomic evidence - Da-Young Han; Suin Cho; Sang-Ho Kim (Metabolic Brain Disease, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Enhanced chlorine photolysis and 1H-benzotriazole degradation in water under the Far-UVC (UV222) irradiation - Jia-Jing Lyu; Qing Bai; Qian-Yuan Wu; Yu-Jia Nong; Mu-Da Han; Min-Yong Lee; Zhong-Quan Ren; Jiang-Lei Xiong; Wen-Long Wang (Journal of Environmental Chemical Engineering, 2026)

Correction: A 3D Printed Poly(ε-caprolactone)-Collagen Hybrid Mesh (TissueDerm) for Breast Reconstruction after Mastectomy in a Pig Model - Kyu-Sik Shim; Han-Saem Jo; Shin Hyun Kim; Dohyun Kim; Yong-Kyu Park; Da-Hye Ryu; Won-Jai Lee; Tai-Suk Roh; Wooyeol Baek (Tissue Engineering and Regenerative Medicine, 2026)

Machine learning-enhanced UAV multispectral remote sensing for monitoring rice leaf area index across critical growth stages - Chao Su; Zaiying Ling; Liwang Han; Yanmin Shuai; Jianguang Wen; Xingwen Lin; Haifeng Tang; Alexandre Maniçoba da Rosa Ferraz Jardim; Hoi Leong Lee; Xuguang Tang (Precision Agriculture, 2026)

The jamming and spoofing of GNSS in Persian Gulf during the Israel-Iran conflict: an analysis by receiver data - Da Xu; Hongqing Li; Yongchun Wang; Dong Huang; Han Zhao; Jiageng Chi; Qiong Wu (Advances in Space Research, 2026)

Allergen regulations for non-prepacked foods in the food service sector: A global scoping review - Mariana Scudeller Vicentini; Carolina Neves Freiria; Jan Mei Soon-Sinclair; Iain Malcolm Ferris; Lisa Marie Winnall; Han Wen; Diogo Thimoteo da Cunha (Food Policy, 2026)

A modified suction caisson penetrating in clay simulated by large deformation method - Zihao Zhao; Jing-chun Han; Jim Shiau; Li-jun Ke; Da-yong Li (Marine Georesources & Geotechnology, 2026)

Laboratory selection reveals flubendiamide resistance, fitness costs, and detoxification-related mechanisms in Spodoptera frugiperda: Insights for insecticide resistance management - Xiaoqi Wang; Peng Song; Boyang An; Guy Smagghe; Shipeng Han; Shanshan Feng; Qiuju Qin; Da Wang; Yunzhuan He (Pesticide Biochemistry and Physiology, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Gene Regulatory Networks Controlling Fruit Anthocyanin Accumulation: A Review - Da Zhang; Bowei Zhu; Xin Liu; Han Wang; Guodong Zhao; Lin’guang Jia; Dongmei Chen; Tongsheng Zhao; Gang Niu; Chaohong Zhang; Xinsheng Zhang (Applied Fruit Science, 2026)

First record of Pseudadenoides kofoidii, a marine sand-dwelling dinoflagellate, from Geoje Island, Korea: morphology, phylogeny, and growth and fatty acid content under different temperature conditions - Da Bin Choi; Minseok Jeong; Zhun Li; Kyong Ha Han; Minjae Kim; Pung-Guk Jang; Joo-Eun Woo; Joo Yeon Youn; Bum Soo Park; Jin Ho Kim; Joo-Hwan Kim; Hyeon Ho Shin (Algae, 2026)
To clarify an unidentified marine sand-dwelling dinoflagellate isolated from samples collected at a sandy beach of Geoje Island, Korea, its morphology and molecular phylogeny based on the small and partial large subunit rRNA gene sequences were examined. In addition, growth responses and fatty acid content of the isolate under different temperature conditions were investigated to assess its physiological traits and aquaculture potential. Cells were 26.3–41.5 μm long (34.8 ± 3.6 μm) and 19.8–40.8 μm deep (28.9 ± 4.8 μm), and a nucleus located in the dorsal half of the cell and pyrenoid surrounded by a starch sheath were observed. Scanning electron microscope observations revealed that the cells were characterized by a lack of precingular plates, scattered thecal pores, a single flagellar pore and a shallow anterior cingulum. One or two pores were present on the plate 3p, and one pore was consistently observed on plate 4p. The phylogenetic analyses revealed that the Korean isolate can be identified as Pseudadenoides kofoidii that has not previously been described in Korean coastal area. In the growth experiments, the isolate appeared to prefer moderate temperatures (15 and 20°C) rather than higher temperature (25°C). Although this species exhibited temperature-dependent variation in docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) production, P. kofoidii maintained remarkably high levels of DHA and EPA in its fatty acid composition (>42% of total fatty acids), highlighting its potential as a promising marine source of fatty acids for aquaculture applications.

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

In situ amidation of NH3 in biogas on sludge-derived carbon to promote coexisting CO2 adsorption - Zhangliang Han; Aoran Zhang; Shuofei Yuan; Xinyue Lu; Shuangxi Fang; Juntao Tang; Da Wang; Zhiqiao He; Feilong Dong; Shuang Song (Water Research, 2026)

Study on the dynamic characteristics of thermal oxidation deposition of aviation kerosene in variable cross-section channels - Xuanyang Zou; Jiali Yang; Huaizhi Han; Da He (Fuel, 2026)

Potent dual-function of marine peptide N6NH2 and its D-enantiomer to combat MDR A. veronii infection in tilapia (GIFT, Oreochromis niloticus) - Ting Li; Na Yang; Da Teng; Ruoyu Mao; Ya Hao; Huihui Han; Yankang Wu; Xiumin Wang; Jianhua Wang (Fish & Shellfish Immunology, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Co-infection of feline coronavirus with feline parvovirus alters plaque phenotypes and single-nucleotide-variant frequencies compared with single infection in CRFK cells - Ha Yeon Kim; Van Thi Lo; Seong Sik Jang; Min Chan Kim; Alain Chrysler Chamfort; Da Young Mun; Min Chang Kang; Han Byul Lee; Dae Gwin Jeong; Hyoung Joon Moon; Hye Kwon Kim (Toxicology and Environmental Health Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Inhibitors Enable Rapid Start-up and Stable Operation of Partial Nitrification: Effects, Mechanisms and Challenges - Yun Song; Xiaoyu Han; Shujun Zhang; Liang Zhang; Bo Wang; Da Kang; Zheng Ge; Yongzhen Peng (Journal of Environmental Sciences, 2026)

Hydration-driven structural engineering via enzymatic glycation: Sustained quercetin release in pullulan-zein coatings for extended walnut preservation - Zi-han Wang; Xue-li Liu; Rui-qi Sun; Bin Qi; Jun-xia Xia; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Distribution, assessment, and sources of nutrients in river water in the headwaters of the Shule River Basin, Northeastern Qinghai-Tibet Plateau - Qin Yang; Donghui Shangguan; Tianding Han; Da Li; Asim Qayyum Butt (Journal of Environmental Sciences, 2026)

A 3D Printed Poly(ε-caprolactone)-Collagen Hybrid Mesh (TissueDerm) for Breast Reconstruction after Mastectomy in a Pig Model - Kyu-Sik Shim; Han-Saem Jo; Shin Hyun Kim; Dohyun Kim; Yong-Kyu Park; Da-Hye Ryu; Won-Jai Lee; Tai-Suk Roh; Wooyeol Baek (Tissue Engineering and Regenerative Medicine, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Buccal application of microneedles coated with an optimized hydrogel containing naproxen and dexamethasone - Joo-Young Kim; Yun-Sik Um; Young-Guk Na; Da-Eun Kim; Yo Han Song; Suyeon Hwang; Minki Jin; Jooyoung Kim; Seung-Ki Baek; Jong-Suep Baek; Hong-Ki Lee; Cheong-Weon Cho (Drug Delivery and Translational Research, 2026)

Molecular Mechanisms and Therapeutic Strategies Targeting Cardiac Lymphangiogenesis in Heart Failure - Meng-Han Chien; Da Liu; Zhenzhong Zheng; Zhen Song; Ming-Qi Zheng; Wenyao Wang (Cardiovascular Toxicology, 2026)

Effect of lipid oxidation on the color deterioration of ready-to-eat oysters: Discussion based on the model system - Ying Luo; Jie Xu; Ying-Chen Fan; Zong-Han Wang; Yuan-Yuan Hu; De-Yang Li; Yu-Xin Liu; Da-Yong Zhou (Food Chemistry, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Dynamic 3-hydroxyflavone-modified D-alanine nanoparticles for metabolic-incorporation in anaerobic, pathogenic biofilms generating CO in infected periodontal pockets - Da-Yuan Wang; Jing Li; Xiao-Han Tian; Siyu Zhang; Yao Chen; Feihe Ma; Henk.J. Busscher; Jing Shen; Linqi Shi (Chemical Engineering Journal, 2025)

First Report of Scrippsiella irregularis Attaran-Fariman & Bolch (Dinophyceae) from Korean Coastal Waters - Minseok Jeong; Da Bin Choi; Zhun Li; Kyong Ha Han; Jinik Hwang; Hyeon Ho Shin (Ocean Science Journal, 2025)

Analysis of the Volatile Aroma Components in ‘Yuguan’ Apple Fruit by Gas Chromatography–Mass Spectrometry - Xin Liu; Da Zhang; Jie Li; Dongmei Chen; Chaohong Zhang; Guodong Zhao; Linguang Jia; Han Wang; Xumin Wang; Tongsheng Zhao; Xinsheng Zhang (Applied Fruit Science, 2025)

Nonlinear theoretical model for predicting the progressive damage of composite pipes in deep-sea mining - Haibo Sun; Yingying Wang; Da Li; Lusheng Jia; Hanchen Zhou; Junjie Han (Ocean Engineering, 2025)

Divergent drought-induced suppression on vegetation and associated feedbacks: Satellite-based observations in 2022 across the Yangtze River basin, China - Lei Han; Yanan Chen; Chaoyang Wu; Li Yao; Ying Wang; Chao Su; Xuan Li; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; Xuguang Tang (Journal of Hydrology, 2025)

Exploration of 2-Mercaptoquinazolin-4(3H)-one Based N-Hydroxyheptanamides as Histone Deacetylase Inhibitors: Design, Synthesis, and Anticancer Bioevaluation - Le Thi Thao; Hwa Kyung Kim; Hoang Kim Ngoc; Da Hyeon Kang; Ha Young Kim; Jong Soon Kang; Duong Tien Anh; Truong Thanh Tung; Sang-Bae Han; Nguyen-Hai Nam (Pharmaceutical Research, 2025)

Association Between ABCG2 Polymorphism and Statin-Induced Adverse Events: A Meta-Analysis - Da Hoon Lee; Hae Ji Shin; Beom Yoon; Han Wool Kim; Hyeon Woo Jo; Hee Jung Kim; Woorim Kim (Cardiovascular Toxicology, 2025)

Functional activities of Lacticaseibacillus casei in culture of Oplegnathus punctatus - Yin Han; Duoxiang Zhao; Da Liang; Yuanyuan Sun; Wenjie Wang; Jiansong Chu; Zizhong Qi (Aquaculture International, 2025)

Two undescribed phytoecdysteroids from Dianthus superbus L. - Yi-Han Liu; Qing Zhang; Da-Zhi Zhang; Xu-Yang Fu; Wu-Yang Liu; Jun-Mian Tian (Phytochemistry Letters, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Mechanical response of tunnel surrounding rock under blasting disturbance with different stress conditions based on acoustic emission and digital image correlation - Tian-xiao Chen; Shi-da Xu; Ben-guo He; Yuan-hui Li; Han Lei (Engineering Geology, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Seismic Data Interpolation by AVO-Preserving Hyperbolic Radon Transform Using FISTA and Polynomial Fitting - Sheng-chao Wang; Han-feng Liu; De-fu Zhang; Hui Sun; Wei Zhang; Song-da Ji (Applied Geophysics, 2025)

Reanalysis-data-based approach to generate urban local weather data to support building energy design in a tropical climate - Xing Zheng; Naika Meili; Shuyang Li; Huanhuan Wang; Lei Xu; Zhen Han; Martín Mosteiro-Romero; Yi Wu; Da Yan; Dengkai Chi; Guanli Feng; Rudi Stouffs (Sustainable Cities and Society, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Fabrication of Ti-MOF/Ti3C2 heterojunction with boosted activity for visible light-driven photocatalytic degradation - Xianghan Cheng; Zhongmin Liu; Ruilin Wang; Yajun Guo; Wenyuan Han; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Suijun Liu; Longlong Geng (Journal of Environmental Chemical Engineering, 2025)

High entropy alloy supported ruthenium single-atoms for enhanced electrochemical hydrogen evolution reaction - Yizhong Zou; Han Zhao; Wen-Da Zhang; Qingna Gong; Jiangyong Liu; Xiaoping Yang; Jing Wang; Xiaodong Yan (Chemical Engineering Journal, 2025)

Assessment of heavy metal contamination and health risks in urban road dust and green belt soil: a case study in Harbin City, China - Ye Zhang; Si-Da Meng; Jian-Xin Wang; Jie Hu; Han Wu; Vasiliy Egorovich Kolodeznikov; Evgeniy Sergeevich Zakharov; Sakhayana Nikolaevna Danilova; Zhong-Hua Tang; Zi-Feng Zhang (Environmental Geochemistry and Health, 2025)

Simulation analysis on synergistic energy-saving effect of building envelope insulation and radiative cooling technology - Han Li; Jingjing An; Chuang Wang; Da Yan (Energy and Buildings, 2025)

In-situ ion-assisted sol-gel method for homogeneous CeO2 mesopore membrane - Huanyu Zhou; Xiaolian Jiang; Qing Han; Minghui Qiu; Xiaowei Da; Xianfu Chen; Yiqun Fan (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Analysis of current technology status for the industrialization of cultured meat - Da Young Lee; Jinmo Park; Dahee Han; Yeongwoo Choi; Jin Soo Kim; Ermie Mariano; Juhyun Lee; Seung Hyeon Yun; Seung Yun Lee; Sungkwon Park; Suk Ho Bhang; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

CD38 Coordinates with NF-κB to Promote Cochlear Inflammation in Noise-Induced Hearing Loss: the Protective Effect of Apigenin - Da Liu; Na Sai; Ying Zhou; Ning Yu; Qing-qing Jiang; Wei Sun; Wei-ju Han; Weiwei Guo (Molecular Neurobiology, 2025)

Performance of cut-off walls under long-term vacuum suction: A case study - Chenchen Xu; Yongtao Hu; Shijie Han; Geng Xueyu; Da Cheng; Ning He; Yongfeng Deng (Marine Georesources & Geotechnology, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Enhanced nonradical oxidation of thiocyanate by nano γ-Fe2O3 and Fe3C-modified 2D hierarchical porous carbon nanosheets - Yang Yang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Shuang Cui; Yina Li; Binchuan Li; Shicheng Wei; Da Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Fluorapatite fingerprints on magmatic-hydrothermal fluid evolution of the Lianyunshan Nb-Ta-Sn deposit, NE Hunan (South China) - Nuerkanati Madayipu; Huan Li; Thomas J. Algeo; Safiyanu Muhammad Elatikpo; Han Zheng; Biao Liu; Da-Peng Zhu; Nuo Li; Victor Ikechukwu Vincent (Chemical Geology, 2025)

Comprehensive assessment of the significance of cellular senescence-associated genes in neuroblastoma - Yahui Han; Biyun Li; Xiaokun Yu; Jianing Liu; Menghui Zhang; Wei Zhao; Da Zhang; Jiao Zhang (Genes & Genomics, 2025)

Plasma Extracellular Matrix Protein 2 Level as a Predictive Biomarker for Rupture of Small Intracranial Aneurysms - Chenchen Wang; Yuwei Han; Da Huo; Xiaoming Li; Guobiao Liang (Journal of Molecular Neuroscience, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Inhibition effect of Botrytis cinerea and quality preservation of grape by Bletilla striata polysaccharide - Da Li; Yanli Zheng; Xuemei Han; Haiyu Ji; Xiaoxiang Su; Zhou Yuan; Kejing Yang; Xiaoyu Jia (Physiological and Molecular Plant Pathology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

A review on the characterization of edible scaffolds for cultured meat: Physical, chemical, biocompatibility, and food safety evaluation methods - Ermie Mariano; Da Young Lee; Juhyun Lee; Yeongwoo Choi; Jinmo Park; Dahee Han; Jin Soo Kim; Ji Won Park; Seok Namkung; Sun Jin Hur (Food Chemistry, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Tailoring oxygen vacancies of W-doped TiO2 to stabilize Ir for boosting oxygen evolution activity in proton-exchange membrane water electrolysis - Jae-Ik Han; Deok-Hye Park; Da-Mi Lim; Yoonhi Gu; Seon-Ha Park; Chan-Eui Hong; Dong-Geon Seo; Ji-Hwan Kim; Jae-Sung Jang; Eo-Jin Kim; Ji-Woong Yun; Hyun-Moon Jo; et al. (Chemical Engineering Journal, 2025)

Covalent organic frameworks supported geminal-atom catalysts for upcycling nitrate into single-cell protein - Jing-Dong Feng; Wen-Da Zhang; Han Zhao; Bixuan Gu; Yong Liu; Xiaomei Lyu; Huan Pang; Liangliang Xu; Zhi-Guo Gu (Chemical Engineering Journal, 2025)

Electrospun 1D Al-LLZO incorporated PVDF-HFP composite electrolyte with fast Li+ pathway derived from highway-traction effect for high performance lithium metal batteries - Joo-Young Han; Sunghoon Kim; Dae Ung Park; Dongwoo Kang; Ji-Hui Oh; Da-Eun Hyun; Dong-Won Lee; Hwiyun Im; Jong-Min Oh; Sang-Mo Koo; Jeonghyun Kim; Jong Ho Won; et al. (Chemical Engineering Journal, 2025)

Influence of wildfire ash concentration on development, survival, and skin and gut microbiota of Rana dybowskii - Qing Tong; Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xiao-yun Han; Li-yong Cui (Science of The Total Environment, 2025)

Unveiling the surface reconstruction of CoWO4 on electrocatalytic nitrate reduction reaction - Qingna Gong; Han Zhao; Wen-Da Zhang; Jing-Dong Feng; Yiguo Zhang; Ying Zhang; Jiangyong Liu; Bing Liu; Jiangwei Zhang; Xiaoping Yang; Jing Wang; Xiaodong Yan (Chemical Engineering Journal, 2025)

Evaluation of acute, repeated dose 28-day and 13-week oral toxicity and genotoxicity of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora - Ju Gyeong Kim; Su-Bin Bak; Gyoung-Deuck Kim; Han-Sol Choi; Da-Ae Kwon; Ha-Young Kim; Dong-Won Son; Jang-Hun Jeong; Byung-Woo Lee; Hyo-Jin An; Hak Sung Lee (Toxicological Research, 2025)
HemoHIM is a functional food ingredient comprising a triple herbal combination of extracts from Angelica gigas Nakai, Cnidium officinale Makino, and Paeonia lactiflora Pallas. It was developed to aid the recovery of impaired immune function. Although it is widely used to treat various immune disorders in Korea, its potential toxicity has not been extensively investigated. Therefore, a comprehensive study was conducted to assess the safety of HemoHIM, including acute oral dose toxicity, 28-day and 13-week repeated-dose toxicity, and genotoxicity. To evaluate its safety profile, the dose was increased to 2,000 mg/kg/day, which corresponds to the dose limit for acute toxicity as per the Organization for Economic Cooperation and Development Test Guideline 423. No abnormal findings were observed at the higher doses. For the 28-day and 13-week repeated-dose toxicity studies, HemoHIM was administered at doses of 500, 1,000, and 2,000 mg/kg/day to examine subchronic toxicity in male and female rats. No test item-related clinical signs or mortality was observed at any of the tested doses. Gross pathology, hematology, blood chemistry, and histopathology evaluations further supported the safety of HemoHIM. Therefore, the NOAEL of HemoHIM was considered to be at 2,000 mg/kg/day for both sexes of rats. Bacterial reverse mutation tests, a chromosome aberration test in human peripheral blood lymphocytes, and a mouse micronucleus test were conducted to determine the genotoxicity of HemoHIM, which revealed that HemoHIM was non-mutagenic and non-clastogenic. Collectively, these findings provide valuable evidence to support the safe use of HemoHIM as a functional food ingredient.

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Multi-omics analysis of the effects of low-temperature storage on chilling injury of bitter gourd - Hongwei Wang; Ling Li; Da-Wen Sun; Lili Ma; Lichun Han; Xuelian He; Qing Wang; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

Trajectory Planning Method for Formation Rendezvous of Underactuated Multi-UUV Under Multiple Constraints - Qingzhe Wang; Da Xu; Xiaoran Liu; Gengshi Zhang; Zhao Han (Journal of Marine Science and Engineering, 2024)
The formation rendezvous of multiple underwater unmanned vehicles (UUVs) necessitates comprehensive consideration of various complex constraints, including kinematics, collision avoidance, and communication. However, existing methods inadequately address these constraints, making it challenging to meet practical needs. In response to these issues, this paper presents a rendezvous points allocation method and a trajectory planning method for formation rendezvous based on dynamic parameter particle swarm optimization (DPPSO) optimizing polynomial trajectories. First, various constraints involved in the formation rendezvous of UUVs are defined, including state constraints, velocity constraints, distance constraints, and turning radius constraints. Subsequently, considering the turning radius and heading angle constraints, temporary trajectories for UUVs are generated using the Dubins curve in the rendezvous points allocation. An evaluation function that accounts for trajectory length and uniformity is designed, ultimately resulting in the optimal allocation scheme. Ultimately, the polynomial trajectory planning method generates initial trajectory clusters. By integrating constraints into the DPPSO algorithm’s fitness function, the boundary conditions of the polynomial trajectories are iteratively optimized to derive trajectories that satisfy all constraints. In the simulation, the proposed method was used for rendezvous point assignment in the desired rectangular formation. The simulation results demonstrate that the proposed method provides a rendezvous point assignment solution that meets the design requirements. Furthermore, based on the rendezvous point assignment for the rectangular formation, the method proposed in this paper was applied to trajectory planning for formation rendezvous. The simulation results show that the generated trajectory successfully achieves the formation rendezvous while satisfying multiple constraints.

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

COLREGs-Adaptive trajectory planning and decision-making in maritime autonomous surface ships - Zhepeng Han; Da Wu; Jinfen Zhang; Tao Huang; Qing-Long Han; Mingyang Zhang (Ocean Engineering, 2024)

In situ investigation of ice fractions and water states during partial freezing of pork loins and shrimps - Zhiwei Zhu; Han Zhang; Xiaohui Liu; Qingqing Zeng; Da-Wen Sun; Zhe Wang (Food Chemistry, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Triggering efficient redox cycling and electron transporting in CuCo spinel oxides via oxygen vacancy building for rapid degradation of antibiotics - Longlong Geng; Fengting Geng; Xianghan Cheng; Man Yang; Xiaoli Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Wenyuan Han; Shujuan Zhuang; Yuting Chen; Guangzhi Hu (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Multiomics comprehensive analysis of pre-storage low-temperature on cowpea metabolism - Lichun Han; Zhengrong Wang; Qing Wang; Da-Wen Sun; Xuelian He; Hongwei Wang; Lili Ma; Chunmei Bai; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Species-level understanding of the bacterial community in Daqu based on full-length 16S rRNA gene sequences - Pei-Jie Han; Liang Song; Zhang Wen; Hai-Yan Zhu; Yu-Hua Wei; Jian-Wei Wang; Mei Bai; Lu-Jun Luo; Ju-Wei Wang; Shen-Xi Chen; Xiao-Long You; Da-Yong Han; et al. (Food Microbiology, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Regulating the Ni-O bond length by constructing Ni(OH)2/CNTs heterostructure for enhanced nucleophile electrocatalytic oxidation - Ming Chen; Yizhong Zou; Han Zhao; Wen-Da Zhang; Qingna Gong; Jiangyong Liu; Jing Wang; Xiaodong Yan (Chemical Engineering Journal, 2024)

Self-condensation for enhancing the hydrophilicity of covalent organic polymers and photocatalytic hydrogen generation with unprecedented apparent quantum yield up to 500 nm - Islam M.A. Mekhemer; Ahmed M. Elewa; Mohamed M. Elsenety; Maha Mohamed Samy; Mohamed Gamal Mohamed; Ahmed Fouad Musa; Tse-Fu Huang; Tzu-Chien Wei; Shiao-Wei Kuo; Bo-Han Chen; Shang-Da Yang; Ho-Hsiu Chou (Chemical Engineering Journal, 2024)

Hydrothermal petroleum related to intracontinental magmatism in the Bohai Bay Basin, eastern China - Li Wang; Yuanjia Han; Da Lou; Zhiliang He; Xiaowen Guo; Matthew Steele-MacInnis (Marine and Petroleum Geology, 2024)

Crusting-fabricated three-dimensional soy-based scaffolds for cultured meat production: A preliminary study - Ermie Mariano; Da Young Lee; Seung Hyeon Yun; Juhyun Lee; Yeong Woo Choi; Jinmo Park; Dahee Han; Jin Soo Kim; Inho Choi; Sun Jin Hur (Food Chemistry, 2024)

Deviation entropy-based dynamic multi-model ensemble interval prediction method for quantifying uncertainty of building cooling load - Changcheng Chen; Jingjing An; Xin Zhou; Chuang Wang; Han Li; Da Yan (Energy and Buildings, 2024)

Two-year carcinogenicity study of a novel plasticizer, bis(2-ethylhexyl) cyclohexane-1,4-dicarboxylate (Eco-DEHCH), by oral diet in Han Wistar rats - Da Som Jeong; Ji-Young Lee; Hyo-Jeong Han; Soo Min Ko; Dong Hyun Lee; Yerin Lee; Woo-Chan Son (Regulatory Toxicology and Pharmacology, 2024)

Impact of wildfire ash on skin and gut microbiomes and survival of Rana dybowskii - Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xue-wen Yang; Xiao-yun Han; Li-yong Cui; Qing Tong (Journal of Hazardous Materials, 2024)

Impact of antibiotic therapy on cutaneous and gut microbiota in Rana dybowskii amphibians: Insights and implications - Xin-zhou Long; Wen-jing Dong; Ming-da Xu; Xue-dong Han; Xiao-yun Han; Li-yong Cui; Qing Tong (Aquaculture, 2024)

Rainstorm erosion difference and topographical changes induced by heavy rainfall between afforestation and grassland restoration catchments on the Chinese Loess Plateau - Mingkui Hao; Zhao Jin; Da Luo; Guofan Cao; Chengcheng Jiang; Hao Han; Siqi Yang; Jing Zhang (Geomorphology, 2024)

Photovoltaic induced self-powered gas sensor based on 2D MoS2 incorporated NbSe2 nanorods heterostructure for NH3 gas sensing at room temperature - Adhimoorthy Saravanan; Bohr-Ran Huang; Seung-Kyu Hwang; Deepa Kathiravan; Wesley Wei-Wen Hsiao; Ravichandran Jayachitra; Abebaw Abun; Po-Da Hong; Ali Mohammadi; A.T. Ezhil Vilian; Young-Kyu Han; Yun Suk Huh (Chemical Engineering Journal, 2024)

Optical characteristics of dissolved organic matter in relation to phytoplankton in Lake Erhai, China - Yuying Guan; Ruiming Han; Nannan Jia; Gongliang Yu; Da Huo (Process Safety and Environmental Protection, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Ambient volatile organic compounds in the Seoul metropolitan area of South Korea: Chemical reactivity, risks and source apportionment - Da-Mee Eun; Yun-Sung Han; Ilkwon Nam; YuWoon Chang; Sepyo Lee; Jeong-Hoo Park; Sung Yong Gong; Jong-Sang Youn (Environmental Research, 2024)

Rice straw ash and amphibian health: A deep dive into microbiota changes and potential ecological consequences - Wen-jing Dong; Ming-da Xu; Xue-wen Yang; Xiu-mei Yang; Xin-zhou Long; Xiao-yun Han; Li-yong Cui; Qing Tong (Science of The Total Environment, 2024)

Comammox and unknown ammonia oxidizers contribute to nitrite accumulation in an integrated A-B stage process that incorporates side-stream EBPR (S2EBPR) - Yuan Yan; Jangho Lee; IL Han; Zijian Wang; Guangyu Li; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Anand Patel; Jim McQuarrie; Beverley M. Stinson; et al. (Water Research, 2024)

Targeted Metabolomic Biomarkers for Stroke Subtyping - Eung-Joon Lee; Da Jung Kim; Dong-Wan Kang; Wookjin Yang; Han-Yeong Jeong; Jeong-Min Kim; Sang-Bae Ko; Seung-Hoon Lee; Byung-Woo Yoon; Joo-Youn Cho; Keun-Hwa Jung (Translational Stroke Research, 2024)

Revisiting the role of Acinetobacter spp. in side-stream enhanced biological phosphorus removal (S2EBPR) systems - Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Varun Srinivasan; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Peisheng He; Anand Patel; Charles Bott; et al. (Water Research, 2024)

Impact of calcium addition on the characteristics of hyaluronic acid-based oral films for vitamin D supplementation - Da-Yeon Ahn; Seo-Youn Kang; Jung-Ah Han (Food Hydrocolloids, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Deciphering the effects of hydrological, biogeochemical and anthropogenic factors on nitrogen species in a subtropical watershed using multiple isotopes - Xiuli Yan; Xiaolan Guo; Anqi Yao; Hongyan Bao; Da-Wei Li; Jr-Chuan Huang; Junwen Wu; Li-Li Han; Shuh-Ji Kao (Journal of Hydrology, 2024)

Comparison of the poisoning mechanism of different zinc species on Nb-Doped Ce-Ti SCR catalysts - Ye Jiang; Xin Sun; Guomeng Zhang; Yichao Xu; Xiao Dou; Yanan Liu; Da Han; Zhengda Yang (Fuel, 2024)

Optimization of LSTM Parameters for Flash Flood Forecasting Using Genetic Algorithm - You-Da Jhong; Chang-Shian Chen; Bing-Chen Jhong; Cheng-Han Tsai; Song-Yue Yang (Water Resources Management, 2024)

Construction of methylation driver gene-related prognostic signature and development of a new prognostic stratification strategy in neuroblastoma - Yahui Han; Biyun Li; Jian Cheng; Diming Zhou; Xiafei Yuan; Wei Zhao; Da Zhang; Jiao Zhang (Genes & Genomics, 2024)

Tartaric acid coupled with gibberellin improves remediation efficiency and ensures safe production of crops: A new strategy for phytoremediation - Teng-yue Yuan; Da-juan Wan; Wen-jun Yang; Jiao-feng Gu; Hang Zhou; Peng Zeng; Bo-han Liao (Science of The Total Environment, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

LBM-PFM simulation of the effect of non-condensable gas on the directional crystallization of seawater - Yina Luo; Da Zhang; Han Yuan; Yan Li (Desalination, 2024)

Biosynthesis of l-histidine from marine biomass-derived galactans in metabolically engineered Corynebacterium glutamicum - Minhye Kim; Jun Won Oh; Da Woon Jeong; Byeong-Hyeon Cho; Joonhee Chang; Xiaoyu Shi; Sung Ok Han (Bioresource Technology, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Analysis of research status and trends on marine benthic dinoflagellate toxins: A bibliometric study based on web of science database and VOSviewer - Jing-Qian Tang; Qian-Hui Shen; Yao-Yao Han; Yang Wu; Xiang-Feng He; Da-Wei Li; Yong Huang (Environmental Research, 2023)

Investigation and application of microscopic mechanism of multiple bubble movement on directional frozen crystallization of seawater - Da Zhang; Yan Li; Han Yuan (Desalination, 2023)

Enhancement of PM2.5 source appointment in a large industrial city of Korea by applying the elemental carbon tracer method for positive matrix factorization (PMF) model - Yun-Sung Han; Da-Mee Eun; Greem Lee; Sung Yong Gong; Jong-Sang Youn (Atmospheric Pollution Research, 2023)

Cinnamaldehyde, a major component of Cinnamomum cassia Presl ethanol extract, has the potential to unlock the outbreak of WSSV - Xu Zhang; Ling Hu; Han-Wei Liu; Da-Wei Song; Yu-Feng Shen; Lei Liu; Yang Hu; Jiong Chen (Aquaculture, 2023)

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

Microbial communities and their correlation with flavor compound formation during the mechanized production of light-flavor Baijiu - Lu-Jun Luo; Liang Song; Ying Han; Pan Zhen; Da-Yong Han; Xin Zhao; Xin Zhou; Yu-Hua Wei; Hui-Xin Yu; Pei-Jie Han; Feng-Yan Bai (Food Research International, 2023)

Occupant behavior modules development for coupled simulation in DeST 3.0 - Xiaoyu Jia; Yiqun Pan; Mingya Zhu; Han Zhu; Zhengrong Li; Jingsi Zhang; Xiang Zhou; Song Pan; Chuang Wang; Da Yan; Zejun Wu; Huiyan Deng; et al. (Energy and Buildings, 2023)

Two weeks dose range-finding and four weeks repeated dose oral toxicity study of a novel reversible monoamine oxidase B inhibitor KDS2010 in cynomolgus monkeys - Kyung-Tai Kim; Doo-Wan Cho; Jae-woo Cho; Wan-Jung Im; Da-Hee Kim; Jong-Hyun Park; Ki Duk Park; Young-Su Yang; Su-Cheol Han (Toxicological Research, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Hydrodynamics and sliding posture analysis of the Cambrian arthropod Ercaicunia multinodosa - Yu-Han Li; Zu-Peng Zhou; Da-You Zhai; Robert J. O'Flynn; Jun Tang; Jin-Wei Xu; Xu-Guang Zhou; Yu Liu (Palaeoworld, 2023)

The influence of substrates addition order on colorimetric assay based on MnO2 nanocubes: A novel turn-off H2O2 assay strategy in water-soak foods - Yanfang Zhao; Yucui Zhang; Xin Liang; Da-Peng Yang; Lei Han (Food Chemistry, 2023)

Rice Straw Biochar is More Beneficial to Soil Organic Carbon Accumulation and Stabilization than Rice Straw and Rice Straw Ash - Mengru He; Ya Jiang; Yuhang Han; Wenhao Zhu; Da Meng; Cuilan Li; Hongguang Cai; Jinjing Zhang (Journal of Soil Science and Plant Nutrition, 2023)

Impact of host plants on biological characteristics and Vg/VgR expression of Spodoptera frugiperda - Shi-Peng Han; Ya-Yuan Zhou; Da Wang; Qiu-Ju Qin; Peng Song; Yun-Zhuan He (Journal of Pest Science, 2023)

Continuous NO dual-generation by ZnO nanoparticle conjugated with α-lipoic acid for functional biodegradable vascular stent - Seung-Woon Baek; Da-Seul Kim; Jun-Kyu Lee; Jun Hyuk Kim; Semi Lee; Jeong Min Park; So-Yeon Park; Duck Hyun Song; Chun Gwon Park; Dong Keun Han (Chemical Engineering Journal, 2023)

UV cross-linked injectable non-swelling dihydrocaffeic acid grafted chitosan hydrogel for promoting wound healing - Jianqun Wang; Wenxia Xu; Wenxuan Zhang; Junlong Da; Lixue Liu; Xiaowei Huang; Chubo Yang; Yuanbo Zhan; Han Jin; Ying Li; Bin Zhang (Carbohydrate Polymers, 2023)

Breast Tissue Reconstruction Using Polycaprolactone Ball Scaffolds in a Partial Mastectomy Pig Model - Kyu-Sik Shim; Da Hye Ryu; Han-Saem Jo; Ki-Bum Kim; Do-Hyun Kim; Yong-Kyu Park; Min Heo; Hee-Eun Cho; Eul-Sik Yoon; Won Jai Lee; Tai Suk Roh; Seung Yong Song; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Hongjam prevents hepatic damage against ethanol-induced fatty liver disease in rats - Da-Young Lee; Moon-Young Song; Young-Min Han; Eun-Hee Kim (Journal of Asia-Pacific Entomology, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Development of an Antarctic krill oil based self-microemulsion drug delivery system and its enhancement of bioaccessibility for curcumin - Dong-wen Fu; Ye Tian; Zi-han Wang; Jin-zhe Li; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Bioscience, 2023)

Evaluation of the 52-week chronic toxicity of a novel phthalate-free plasticizer, Eco-DEHCH (bis(2-ethylhexyl) cyclohexane-1,4-dicarboxylate), in Han Wistar rats - Ji-Young Lee; Hyo-Jeong Han; Soo Min Ko; Da Som Jeong; Jiyeon Kang; Dong Hyun Lee; Hwa Jun Cha; Woo-Chan Son (Food and Chemical Toxicology, 2023)

Nitrate induced precise atom substitution and vacancies for overall water splitting - Ya-Nan Zhou; Yi-Wen Dong; Yang Wu; Bin Dong; Hai-Jun Liu; Xue-Jun Zhai; Guan-Qun Han; Da-Peng Liu; Yong-Ming Chai (Chemical Engineering Journal, 2023)

Soil erosion differences in paired grassland and forestland catchments on the Chinese Loess Plateau - Si-qi Yang; Da Luo; Hao Han; Zhao Jin (Journal of Mountain Science, 2023)

Typhoon Case Comparison Analysis Between Heterogeneous Many-Core and Homogenous Multicore Supercomputing Platforms - Xin Liu; Xiaolin Yu; Haoran Zhao; Qiqi Han; Jie Zhang; Chengzhi Wang; Weiwei Ma; Da Xu (Journal of Ocean University of China, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

Extract of Styrax japonica attenuates glutamate-induced apoptosis via regulating MAPK signaling pathway in HT22 hippocampal cells - Da Hye Jeong; Song-I Han; Jae-Hoon Kim (Plant Biotechnology Reports, 2023)
Two-thirds of people with dementia suffer from Alzheimer’s disease, and there is a need to develop treatments with fewer side effects. Cholinergic and glutamate-induced brain damage occurs in the early stages of Alzheimer’s disease, so substances that suppress these symptoms may be potential candidates for the treatment. Ethanol extracts of 40 kinds of oriental medicine plants were examined whether they have acetylcholine esterase (Ache) inhibitory properties. We next investigated whether the ethanol extracts of six oriental medicine plants showing Ache inhibitory activity could inhibit glutamate-induced HT22 cell death. The ethanol extract of Styrax japonica (EESJ) was found to be relatively superior in both inhibitory activities. MTT and annexin V/PI staining assays confirmed that EESJ inhibited glutamate-induced apoptosis in the HT22 mouse hippocampal cells. EESJ also suppressed glutamate-mediated ROS production and attenuated the phosphorylation levels of MAPK members including ERK, JNK, and p38 kinases. Therefore, EESJ is a suitable candidate for developing a substance of Alzheimer’s disease treatment.

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Genotoxicity assessment of root extracts of Paeonia lactiflora Pall - Su-Min Bak; Seng-Min Back; Da Yeon Kim; Na-Young Jeung; Nan-Young Kim; Jun-Young Yang; Kang-Hyun Han; Yong-Bum Kim; Byung Sun Min; Byoung-Seok Lee; Seong-Hoon Park (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

ε-Poly( -lysine)-based bioreducible nanogels for mitochondria-targeted delivery and release: Hydrophobicity-tuned nucleus-to-mitochondria organelle-targeting switch and slow disulfide cleavage - Hana Cho; Yeon Su Choi; Da Gyeom Choung; Won Gu Choi; Min Seo Lee; Yong-Yeon Cho; Joo Young Lee; Hye Suk Lee; Han Chang Kang (Chemical Engineering Journal, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Identification of Key Genes Associated with Risk and Prognosis of Neuroblastoma - Jiao Zhang; Yahui Han; Dun Yan; Diming Zhou; Xiafei Yuan; Wei Zhao; Da Zhang (Journal of Molecular Neuroscience, 2022)

A Two-Stage Path Planning Algorithm Based on Rapid-Exploring Random Tree for Ships Navigating in Multi-Obstacle Water Areas Considering COLREGs - Jinfen Zhang; Han Zhang; Jiongjiong Liu; Da Wu; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
A two-stage ship path planning method is proposed, based on the Rapid-exploring Random Tree (RRT) algorithm, which is composed of global path planning and local path planning, addressing the important problem of finding an economical and safe path from start to destination for ships under dynamic environment, especially in waters with multiple obstacles and multiple target ships. The global path planning takes into consideration the ship draft and Under Keel Clearance to find navigable water using RRT, and reduces the path length and waypoints based on elliptic sampling and smoothing. In the local path planning, a dynamic collision risk detection model is constructed by introducing the Quaternion Ship Domain under a dynamic environment, and the restrictions of ship manoeuvrability and COLREGs are also involved. The simulation results show that the proposed model can find a satisfactory path within a few iterations, and keep clear of both static obstacles and dynamic ships. The research can be used to make and verify planned ship routes before sailing and to guide officers to make decisions regarding collision avoidance.

An Exploratory Survey on the Care for Ataxic Patients in the American Continents and the Caribbean - Laura Bannach Jardim; Ali Hasan; Sheng-han Kuo; Jonathan Javier Magaña; Marcondes França; Wilson Marques; Claudia Camejo; Luiz Carlos Santana-da-Silva; Emília Embiruçu Leão; Gisele Espíndola; Francisca Canals; Marcelo Miranda; et al. (The Cerebellum, 2022)

Brevibacillus dissolubilis sp. nov., Isolated from Fresh Water - Wei Li; Zhao-Xuan Wang; Fu Ma; Zhi-Da Zi; Han-Yi Chen; De Zhou; Jie Lv (Current Microbiology, 2022)

Fat Graft with Allograft Adipose Matrix and Magnesium Hydroxide-Incorporated PLGA Microspheres for Effective Soft Tissue Reconstruction - Dae-Hee Kim; Da-Seul Kim; Hyun-Jeong Ha; Ji-Won Jung; Seung-Woon Baek; Seung Hwa Baek; Tae-Hyung Kim; Jung Chan Lee; Euna Hwang; Dong Keun Han (Tissue Engineering and Regenerative Medicine, 2022)

Mesenchymal-to-epithelial transition of osteoblasts induced by Fam20c knockout - Ya-Wei Geng; Zhen Zhang; Han Jin; Jun-Long Da; Kai Zhang; Jian-Qun Wang; Yu-Yao Guo; Bin Zhang; Ying Li (Genes & Genomics, 2022)

CRISPR/Cas9-mediated mutation of 5-oxoprolinase gene confers resistance to sulfonamide compounds in Arabidopsis - Ga-Jin Baeg; Seong-Hyeon Kim; Da-Min Choi; Sharanya Tripathi; Yun-Jeong Han; Jeong-Il Kim (Plant Biotechnology Reports, 2021)

Correction to: TAK1 is involved in sodium L‑lactate‑stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Generation of Hepatic Progenitor Cells from the Primary Hepatocytes of Nonhuman Primates Using Small Molecules - Da Hee Hong; Changhee Lee; Yohan Kim; Seung Bum Lee; Su-Cheol Han; Sung Joo Kim; Heung-Mo Yang; Dongho Choi; Jaemin Jeong; Kiyoung Ryu (Tissue Engineering and Regenerative Medicine, 2021)

Generation and Characterization of a Specific Polyclonal Antibody against Arabidopsis thaliana Phytochrome-Interacting Factor 3 - Da-Min Choi; Jae-Yong Cho; Woe-Yeon Kim; Yun-Jeong Han; Jeong-Il Kim (Journal of Plant Biology, 2021)

Fungal diversity on the surface of saffron corms with different growth characteristics - Han Shuwen; Zhou Qing; Liu Jin; Da Miao (Plant Biosystems, 2021)

TAK1 is involved in sodium L-lactate-stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

A new cyclic peptide from the fibrous root of Pseudostellaria heterophylla - Xiao-fei Zhao; Qian Zhang; Han-tao Zhao; Yan-da Zhang; Han-ru Liu; Lu-jiang Yuan; Qian-feng Chen (Natural Product Research, 2020)

Fucoxanthin Mitigates Subarachnoid Hemorrhage-Induced Oxidative Damage via Sirtuin 1-Dependent Pathway - Xiang-Sheng Zhang; Yue Lu; Tao Tao; Han Wang; Guang-Jie Liu; Xun-Zhi Liu; Cang Liu; Da-Yong Xia; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2020)

Transcriptomic analysis of the effect of (E)-3-(3,5-dimethoxyphenyl)-1-(2-methoxyphenyl) prop-2-en-1-one (DPP23) on reactive oxygen species generation in MIA PaCa-2 pancreatic cancer cells - Hongnam Sim; Euitaek Jung; Da Hyun Lee; Ji Hye Choi; Young Han Lee; Soon Young Shin (Genes & Genomics, 2020)

Inhibition of orf virus replication in goat skin fibroblast cells by the HSPA1B protein, as demonstrated by iTRAQ-based quantitative proteome analysis - Jun-hong Hao; Han-jin Kong; Ming-hao Yan; Chao-chao Shen; Guo-wei Xu; Da-jun Zhang; Ke-shan Zhang; Hai-xue Zheng; Xiang-tao Liu (Archives of Virology, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Probiotic and Safety Properties Screening of Enterococcus faecalis from Healthy Chinese Infants - Juan Wang; Rong Da; Xiaohong Tuo; Yue Cheng; Jie Wei; Kaichong Jiang; Jia Lv; Omolade Monisayo Adediji; Bei Han (Probiotics and Antimicrobial Proteins, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Diet differences between males and females in sexually dimorphic ungulates: a case study on Siberian ibex - Lei Han; David Blank; Muyang Wang; António Alves da Silva; Weikang Yang; Kathreen Ruckstuhl; Joana Alves (European Journal of Wildlife Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A critical review on environmental implications, recycling strategies, and ecological remediation for mine tailings - Da-Mao Xu; Chang-Lin Zhan; Hong-Xia Liu; Han-Zhi Lin (Environmental Science and Pollution Research, 2019)

Ore genesis and tectonic setting of the Laojiagou porphyry molybdenum deposit, Inner Mongolia, China: evidence from geology, fluid inclusions, H–O isotopes, zircon U–Pb geochronology, and geochemistry - Wen-Hao Tang; Jian Li; Ke-Yong Wang; Shun-Da Li; Wen-Yan Cai; Han-Lun Liu; Yi-Cun Wang (Arabian Journal of Geosciences, 2019)

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Polyhalogenated Carbazoles in Surface Sediment from Sanmen Bay, East China Sea: Spatial Distribution and Congener Profile - Yong Qiu; Kunyan Liu; Shanshan Zhou; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

The apple U-box E3 ubiquitin ligase MdPUB29 contributes to activate plant immune response to the fungal pathogen Botryosphaeria dothidea - Peng-Liang Han; Yuan-Hua Dong; Kai-Di Gu; Jian-Qiang Yu; Da-Gang Hu; Yu-Jin Hao (Planta, 2019)

Activities and conformation changes of food enzymes induced by cold plasma: A review - Yongxu Han; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2019)

Physiological differences in the growth and maturation of Eisenia bicyclis and Ecklonia cava gametophytes in Korea - Han Gil Choi; Da Vine Jeon; Seo Kyoung Park; Xu Gao (Journal of Oceanology and Limnology, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

A siphonous morphology affects light-harvesting modulation in the intertidal green macroalga Bryopsis corticulans (Ulvophyceae) - Vasco Giovagnetti; Guangye Han; Maxwell A. Ware; Petra Ungerer; Xiaochun Qin; Wen-Da Wang; Tingyun Kuang; Jian-Ren Shen; Alexander V. Ruban (Planta, 2018)

Integration of Bacterial Expansin on Agarolytic Complexes to Enhance the Degrading Activity of Red Algae by Control of Gelling Properties - Da Woon Jeong; Jeong Eun Hyeon; Young-Chul Joo; Sang Kyu Shin; Sung Ok Han (Marine Biotechnology, 2018)

Notch ligand Delta-like1 enhances degranulation and cytokine production through a novel Notch/Dok-1/MAPKs pathway in vitro - Songsong Jiang; Yifan Da; Shiwen Han; Yahong He; Huilian Che (Immunologic Research, 2018)

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Mental Stress from Animal Experiments: a Survey with Korean Researchers - Minji Kang; AhRam Han; Da-eun Kim; Troy Seidle; Kyung-Min Lim; SeungJin Bae (Toxicological Research, 2018)

Will elevated atmospheric CO2 boost the growth of an invasive submerged macrophyte Cabomba caroliniana under the interference of phytoplankton? - Xin Liu; Yanqing Han; Jinge Zhu; Jiancai Deng; Weiping Hu; Thomaz Edson Veloso da Silva (Environmental Science and Pollution Research, 2018)

Investigation of the anisotropy of black shale in dynamic tensile strength - Xiaoshan Shi; Da’an Liu; Wei Yao; Yirui Shi; Tiewu Tang; Bonan Wang; Weige Han (Arabian Journal of Geosciences, 2018)

Effects of wind fences on the wind environment around Jang Bogo Antarctic Research Station - Jang-Woon Wang; Jae-Jin Kim; Wonsik Choi; Da-Som Mun; Jung-Eun Kang; Hataek Kwon; Jin-Soo Kim; Kyung-Soo Han (Advances in Atmospheric Sciences, 2017)

Contaminant characteristics and environmental risk assessment of heavy metals in the paddy soils from lead (Pb)-zinc (Zn) mining areas in Guangdong Province, South China - Da-Mao Xu; Bo Yan; Tao Chen; Chang Lei; Han-Zhi Lin; Xian-Ming Xiao (Environmental Science and Pollution Research, 2017)

The phosphodiesterase-4 inhibitor roflumilast decreases ethanol consumption in C57BL/6J mice - Xin Liu; Pi-Da Hao; Ming-Feng Yang; Jing-Yi Sun; Lei-Lei Mao; Cun-Dong Fan; Zong-Yong Zhang; Da-Wei Li; Xiao-Yi Yang; Bao-Liang Sun; Han-Ting Zhang (Psychopharmacology, 2017)

Desorption of micropollutant from spent carbon filters used for water purifier - Da-Sol Kwon; So-Yeon Tak; Jung-Eun Lee; Moon-Kyung Kim; Young Hwa Lee; Doo Won Han; Sanghyeon Kang; Kyung-Duk Zoh (Environmental Science and Pollution Research, 2017)

Improved preconditioned conjugate gradient algorithm and application in 3D inversion of gravity-gradiometry data - Tai-Han Wang; Da-Nian Huang; Guo-Qing Ma; Zhao-Hai Meng; Ye Li (Applied Geophysics, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Molecular epidemiology and phylogenetic analysis of HA gene of influenza A(H1N1)pdm09 strain during 2010–2014 in Dalian, North China - Yan Han; Nan Sun; Qiu-yue Lv; Dan-hong Liu; Da-peng Liu (Virus Genes, 2016)

Valuation of debris flow mitigation measures in tourist towns: a case study on Hongchun gully in southwest China - Ming-li Chen; Gui-sheng Hu; Ning-sheng Chen; Cun-yao Zhao; Song-jiang Zhao; Da-wei Han (Journal of Mountain Science, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Effects of light shading and climatic conditions on the metabolic behavior of flonicamid in red bell pepper - Da-I Jung; Waziha Farha; A. M. Abd El-Aty; Sung-Woo Kim; Md. Musfiqur Rahman; Jeong-Heui Choi; Md. Humayun Kabir; So Jeong Im; Young-Jun Lee; Lieu. T. B. Truong; Ho-Chul Shin; Geon-Jae Im; et al. (Environmental Monitoring and Assessment, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Docetaxel Modulates the Delayed Rectifier Potassium Current (I K) and ATP-Sensitive Potassium Current (I KATP) in Human Breast Cancer Cells - Tao Sun; Zhi-Guo Song; Da-Qing Jiang; Hong-Guang Nie; Dong-Yun Han (The Journal of Membrane Biology, 2015)

Effect of culturing conditions on the expression of key enzymes in the proteolytic system of Lactobacillus bulgaricus - Jun-cai Hou; Fei Liu; Da-xi Ren; Wei-wei Han; Yue-ou Du (Journal of Zhejiang University-SCIENCE B, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

N-3 polyunsaturated fatty acids intake and risk of colorectal cancer: meta-analysis of prospective studies - Guo-Chong Chen; Li-Qiang Qin; Da-Bing Lu; Tie-Mei Han; Yan Zheng; Guo-Zhang Xu; Xiao-Huai Wang (Cancer Causes & Control, 2015)

Ambient noise spectral properties in the north area of Xisha - Lianglong Da; Chao Wang; Mei Han; Lin Zhang (Acta Oceanologica Sinica, 2014)

Combined impacts of antecedent earthquakes and droughts on disastrous debris flows - Ning-sheng Chen; Yang Lu; Hai-bo Zhou; Ming-feng Deng; Da-wei Han (Journal of Mountain Science, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Normalized edge detection, and the horizontal extent and depth of geophysical anomalies - Li-Li Li; Li-Guo Han; Da-Nian Huang (Applied Geophysics, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Effects of position within wheat field and adjacent habitats on the density and diversity of cereal aphids and their natural enemies - Zi-Hua Zhao; Cang Hui; Da-Han He; Feng Ge (BioControl, 2013)

Study on the In Vitro Effects of the Mixtures of Polycyclic Aromatic Hydrocarbons (PAHs) and Heavy Metals on Ethoxyresorufin-O-Deethylase (EROD) Activity in Mossambica tilapia Liver - Da Xiong Han; Hai Yan Wang; Hong Wei Yue; Su Min Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Effects of miR-19b Overexpression on Proliferation, Differentiation, Apoptosis and Wnt/β-Catenin Signaling Pathway in P19 Cell Model of Cardiac Differentiation In Vitro - Da-Ni Qin; Lingmei Qian; De-Liang Hu; Zhang-Bin Yu; Shu-Ping Han; Chun Zhu; Xuejie Wang; Xiaoshan Hu (Cell Biochemistry and Biophysics, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Immunolocalization of chloride transporters to gill epithelia of euryhaline teleosts with opposite salinity-induced Na+/K+-ATPase responses - Cheng-Hao Tang; Lie-Yueh Hwang; I-Da Shen; Yu-Hui Chiu; Tsung-Han Lee (Fish Physiology and Biochemistry, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Metaproteomic characterization of dissolved organic matter in the water column of the South China Sea - Da-Zhi Wang; Hong-Po Dong; Zhang-Xian Xie; Min-Han Dai; Hua-Sheng Hong (Limnology and Oceanography, 2011)
We characterized dissolved organic matter (DOM;

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Molecular cloning and characterization of Izumo1 gene from sheep and cashmere goat reveal alternative splicing - Wan-Jin Xing; Bao-Da Han; Qi Wu; Li Zhao; Xiao-Hong Bao; Shorgan Bou (Molecular Biology Reports, 2011)

Expression of recombinant proteins in plants by using baculovirus vectors - Eun-Yi Oh; Young Kwan Kim; Da-Young Park; Zhe Lu; Young Kug Choo; Yeon Soo Han; Jeong Mee Park; Kisung Ko (Horticulture, Environment, and Biotechnology, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Can the soil seed bank contribute to revegetation of the drawdown zone in the Three Gorges Reservoir Region? - Zhi-Jun Lu; Lian-Fa Li; Ming-Xi Jiang; Han-Dong Huang; Da-Chuan Bao (Plant Ecology, 2010)

Amino Acid Homochirality may be Linked to the Origin of Phosphate-Based Life - Da Xiong Han; Hai Yan Wang; Zhi Liang Ji; An Fu Hu; Yu Fen Zhao (Journal of Molecular Evolution, 2010)

Mesoscale barotropic instability of vortex Rossby waves in tropical cyclones - Wei Zhong; Han-Cheng Lu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2010)

Erratum to: Molecular evolution and functional specialization of chalcone synthase superfamily from Phalaenopsis Orchid - Ying-Ying Han; Feng Ming; Wei Wang; Jing-Wen Wang; Ming-Ming Ye; Da-Leng Shen (Genetica, 2010)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Molecular evolution and functional specialization of chalcone synthase superfamily from Phalaenopsis Orchid - Ying-Ying Han; Feng Ming; Wei Wang; Jing-Wen Wang; Ming-Ming Ye; Da-Leng Shen (Genetica, 2006)

A novel chalcone synthase gene fromPhalaenopsis orchid that alters floral morphology in transgenic tobacco plants - Ying-Ying Han; Feng Ming; Jing-Wen Wang; Ming-Ming Ye; Da-Leng Shen (Plant Molecular Biology Reporter, 2005)

THE CULTURE OF FIBROBLASTS FROM DIAPHRAGM OF GIANT PANDA - Zhi-Ming Han; Da-Yuan Chen; Jin-Song Li; Qing-Yuan Sun; Peng-Yang Wang; Yang Huang; Jun Du (In Vitro Cellular & Developmental Biology - Animal, 2001)

Hair concentrations of calcium, iron, and zinc in pregnant women and effects of supplementation - Po Lau Leung; Han Ming Huang; Da Ze Sun; MeI Guang Zhu (Biological Trace Element Research, 1999)

Hair and serum calcium, iron, copper, and zinc levels during normal pregnancy at three trimesters - Han Ming Huang; Po Lau Leung; Da Ze Sun; Mei Guang Zhu (Biological Trace Element Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)